2007
DOI: 10.1097/00000542-200701000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Lidocaine Infusion Facilitates Acute Rehabilitation after Laparoscopic Colectomy

Abstract: Intravenous lidocaine improves postoperative analgesia, fatigue, and bowel function after laparoscopic colectomy. These benefits are associated with a significant reduction in hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
325
3
29

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 369 publications
(378 citation statements)
references
References 48 publications
21
325
3
29
Order By: Relevance
“…Sevoflurane requirement was significantly reduced during abdominal surgery as monitored by BIS at all intraoperative time points [11]. The same result was found in different types of surgeries using sevoflurane [7,11,32,34] and desflurane [6,22,27]. Similarly, systemic lidocaine allowed Altermatt et al to reduce propofol requirement during the maintenance of total intravenous anesthesia for laparoscopic cholecystectomy as measured by BIS.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Sevoflurane requirement was significantly reduced during abdominal surgery as monitored by BIS at all intraoperative time points [11]. The same result was found in different types of surgeries using sevoflurane [7,11,32,34] and desflurane [6,22,27]. Similarly, systemic lidocaine allowed Altermatt et al to reduce propofol requirement during the maintenance of total intravenous anesthesia for laparoscopic cholecystectomy as measured by BIS.…”
Section: Discussionmentioning
confidence: 70%
“…Uzun et al report that perioperative IV lidocaine infusion had no significant effect on remifentanil use during hypotensive anesthesia for transsphenoidal endoscopic hypophyseal adenoma excision [30]. Kaba et al found that the total dose of sufentanil given to patients in the lidocaine group during laparoscopic colectomy was significantly lower than in the control group (13.0 ± 3.7 µg versus 16.3 ± 3.6 µg) [7]. A similar result was obtained in ambulatory surgery where lidocaine use yielded a 30% reduction in intraoperative opioid use [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Seven studies originated in the USA, [25][26][27][28][29][30][31] one in Belgium, 32 two in Taiwan, 14,33 three in Germany, 23,34,35 one in New Zealand, 36 three in Sweden, [37][38][39] two in China, 40,41 one in France, 42 three in Canada, [43][44][45] one in Mexico, 24 two in Saudi Arabia, 46,47 one in Israel, 48 one in the Republic of Korea 49 and one in Finland. 50 Studies were conducted in patients undergoing abdominal, cardiac, thoracic, orthopedic, or urologic surgery ( Table 1).…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…51 Twenty-six (90%) studies were placebo-controlled blinded studies. 14,[23][24][25][26][27][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][45][46][47][48][49] Primary outcomes…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%